"Rambo root" to the rescue: How a simple, low‐cost solution can lead to multiple sustainable development gains. Issue 2 (20th November 2020) - Villarino, Ma. Eliza J; Da Silva, Mayesse; Becerra Lopez‐Lavalle, Luis Augusto; Castro‐Nuñez, Augusto
Abstract: Rugged and resilient, cassava is a bulky root crop that can thrive on poor soils. Cultivating it offers the potential to restore degraded land, which in turn may reduce hunger, generate livelihoods, fight climate change and even promote peace. As such, farming cassava offers a nature‐based solution that can contribute to achieving numerous sustainable development targets. The authors acknowledge that scaling up production of any commodity may bring risks of deforestation and biodiversity loss through clearing forest areas. In the case of increasing cassava production, though, this may not be the case because cassava can be cultivated on land affected by degradation, and this resource is abundant; policies and initiatives exist to mitigate those risks; and the principal goal is to scale up a sustainable land use system.